bioteknologi Efek Terapi Kombucha Bunga Telang (Clitoria terantea) Sebagai Produk Bioteknologi Pada Konsentrasi dan Kematian Spermatozoa Mencit (Mus musculus) Pasca Paparan Asap Rokok: Efek Terapi Kombucha Bunga Telang (Clitoria terantea) Sebagai Produk Bioteknologi Pada Konsentrasi dan Kematian Spermatozoa Mencit (Mus musculus) Pasca Paparan Asap Rokok - Rezaldi, Firman (SITAWA : Jurnal Farmasi Sains dan Obat Tradisional, 2024)
The cause of health problems or disorders including the lungs, heart, gastrointestinal inflammation and reproductive fertility comes from the bad habit of smoking. A decrease in spermatozoa as an indicator of fertility, both in quality and quantity, is one of the bad effects of cigarette smoke. Consuming or treating food or drinks containing antioxidants in this study has been found to be able to reduce the level of spermatozoa decline in active smokers both in quality and quantity. This study aims to determine the effect of butterfly pea flower kombucha therapy as a source of antioxidants on male mice (Mus musculus) in determining the effect of giving butterfly pea flower kombucha therapy on sperm concentration and death rate after exposure to cigarette smoke. This research has proven that telang flower kombucha given at 4 mL/100 grams BW of male mice has the potential to increase the concentration of spermatozoa and reduce the percentage of abnormal spermatozoa death in mice after being exposed to cigarette smoke for 15 minutes.